2023
DOI: 10.33395/owner.v7i3.1420
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Potensi Pajak Daerah dengan Pendekatan Makro-Mikro di Kota Serang

Abstract: The development of hotel taxes and restaurant taxes in the city of Serang in the last 5 years has shown a decline. In the last 2 years, namely 2022 and 2021, there has been a negative trend, aka a decrease in the percentage of revenue realization. This is not the same as data for 2020, 2019 and 2018, which shows a positive trend in its realization. The research method used is a quantitative method using secondary data obtained from the offices of BAPENDA, BPKAD and DINKOP UKM. This study uses 2 macro and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…Generally, calculating local tax potential through the micro approach involves summing up the tax obligations of all local taxpayers (Anggriawan et al, 2023). The amount of these tax obligations is obtained by multiplying the tax rate by the value of the tax object based on the results of surveys or observations conducted by the local government (Nurlinda & Sinuraya, 2020).…”
Section: Approaches To Calculating Local Tax Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, calculating local tax potential through the micro approach involves summing up the tax obligations of all local taxpayers (Anggriawan et al, 2023). The amount of these tax obligations is obtained by multiplying the tax rate by the value of the tax object based on the results of surveys or observations conducted by the local government (Nurlinda & Sinuraya, 2020).…”
Section: Approaches To Calculating Local Tax Potentialmentioning
confidence: 99%
“…Research conducted in Serang concluded that the projected potential of Hotel Tax for 2022 and 2023 is expected to grow. Hotel Taxes can significantly contribute to local tax revenue if these projections are realized (Anggriawan et al, 2023). Meanwhile, research conducted in Ketapang Regency found a 79.5% untapped potential of Hotel Tax each year during the 2012-2016 period.…”
Section: Introductionmentioning
confidence: 99%